Utilization of combined PD-L1 expression and neutrophil-to-lymphocyte ratio prior to surgery as a prognostic factor in non-small cell lung cancer with brain metastasis - Xia, Lei; Huang, Hu; Xiao, He; Wang, Dong; Yang, Zhenzhou (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: This study was undertaken to investigate the expression of programmed death-ligand 1 (PD- L1) in the pulmonary primary tumor and brain metastases (BM) tumor as well as neutrophil-to-lymphocyte ratio (NLR) in preoperative peripheral blood samples in advanced non-small cell lung cancer. The potential association between both PD-L1 expression and NLR value and therapeutic sensitivity along with prognosis was explored. Methods: Eleven patients pathologically confirmed as non-small cell lung cancer (NSCLC) with BM were enrolled. The expression of PD-L1 in pulmonary primary tumor and BM tumor was evaluated with immunohistochemistry. NLR value was calculated from blood cell count. DFS and OS were calculated using the Kaplan-Meier method, and the log-rank test was used to assess differences between groups. Results: High expression of PD-L1 was observed in 4 pulmonary primary tumors and 3 BM tumors respectively. The NLR in peripheral blood before brain surgery was shown to be efficient to discriminate patients whose brain metastatic lesion reached disease control from others (AUC: 0.917 95% CI: 0.731– 1.000, P=0.041). Five patients had an NLR value higher than the cutoff value of 3.0553. Eight patients with low expression of PD-L1 in BM lesions had 27 months of median OS, which was signifcantly longer than patients with high expression of PD-L1 with 10 months of median OS (Log-Rank, P=0.012). Five patients with both low expression of PD-L1 in BM lesions and low NLR value (≤3.0553) reached 36 months mOS significantly longer than others with only 10 months of mOS (Log-Rank, P=0.034, HR =0.133, 95% CI: 0.861–65.819, P=0.068). Conclusions: High expression of PD-L1 along with high NLR value is associated with less sensitivity of response to treatment and poor prognosis.